The EFFECT OF GROWTH OPPORTUNITY AND OTHER FACTORS ON ACCOUNTING CONSERVATISM - Putri, Helmalia; Karmudiandri , Arwina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to obtain empirical evidence about the effect of institutional ownership, liquidity, growth opportunity, managerial ownership, leverage, and firm size as independent variables on accounting conservatism as the dependent variable. This research uses the market-to-book ratio to measure accounting conservatism. This research uses sample data from companies in the consumer cyclicals and consumer non-cyclicals listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The sample selection in this study used purposive sampling method, resulting in 72 companies that met the criteria and were selected as sample data total 288 data. In testing the hypothesis, this study uses multiple regression method. The result of this study concluded that the independent variable leverage has a positive effect on accounting conservatism, while firm size has a negative effect on accounting conservatism. Meanwhile, the other independent variables institutional ownership, liquidity, growth opportunity and managerial ownership has no affect to accounting conservatism.